ACUTE WATERY DIARRHOEA IN UNDER-FIVE CHILDREN: PERCEPTION OF THE CAUSES, HEALTH SEEKING BEHAVIOURS AND BARRIERS OF MOTHERS TO CARE IN A PRIMARY HEALTH CARE CENTRE IN MAIDUGURI, NIGERIA - MUSTAPHA MG; GARBA MA; ALHAJI MA (Ntec Specialist, 2008)
Background: Acute Watery Diarrhoea (AWD) is usually associated with complications, such as dehydration, electrolyte imbalance and acute renal failure. The WHO definition of home case management for diarrhea includes among others: the recognition of danger signs of diarrhea that requires immediate care and seeking help from an appropriate health facility. Objectives: To examine mothers or care givers perception of the causes of AWD, indications and barriers to health seeking behavior during AWD in under-5(U-5) children in Maiduguri. Methods: The study was carried out in October 2006 at Yerwa Primary Health Care Centre (PHCC) in Maiduguri, Nigeria. Quantitative method by the use of face to face interview was employed. Results: Two hundred mothers or caregivers of U-5 children who presented to the Yerwa PHCC with complaints of AWD in their children or wards were interviewed. Poor hygiene and contaminated food or water were identified as the main cause of AWD. Eighty-five (42.5%) mothers or caregivers reported patronizing herbalist side by side with orthodox medical attention for AWD. The indications for seeking health in 90% of the mothers or caregivers were child being weak and non-response to ORS, while 37.5% declined to give reason. Financial constraints and lack of transportation contributed to the barriers of health seeking. Majority of the women had good knowledge of the causes of childhood AWD, but none knew the course of AWD. Conclusion: Majority of the mothers had barriers to health seeking despite good knowledge of the causes of AWD and indication for seeking health seeking. Appropriate and proper health education in addition to the adoption and practice of the principles of Primary Health Care and full implementation of National Health Insurance Scheme is therefore recommended